2018
DOI: 10.1161/hypertensionaha.117.10306
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Ameliorate Cyclosporine A–Induced Hypertension in Mice

Abstract: The calcineurin inhibitor cyclosporine A (CsA) suppresses the immune system but promotes hypertension, vascular dysfunction, and renal damage. CsA decreases regulatory T cells and this contributes to the development of hypertension. However, CsA's effects on another important regulatory immune cell subset, myeloid-derived suppressor cells (MDSCs), is unknown. We hypothesized that augmenting MDSCs would ameliorate the CsA-induced hypertension and vascular and renal injury and dysfunction and that CsA reduces MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…For example, anti‐thymoglobulin is known to reduce populations of MDSCs, but its primary effect was on PMN‐MDSCs, rather than on M‐MDSCs 3 . Cyclosporine is known to decrease MDSC populations, whereas rapamycin and corticosteroids are known to increase MDSC populations 36,37,40 . Accordingly, we used a model of transplant in which animals did not receive immunosuppression; all animals demonstrated expanded MDSCs and these MDSCs were suppressive of T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, anti‐thymoglobulin is known to reduce populations of MDSCs, but its primary effect was on PMN‐MDSCs, rather than on M‐MDSCs 3 . Cyclosporine is known to decrease MDSC populations, whereas rapamycin and corticosteroids are known to increase MDSC populations 36,37,40 . Accordingly, we used a model of transplant in which animals did not receive immunosuppression; all animals demonstrated expanded MDSCs and these MDSCs were suppressive of T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al demonstrated that a subpopulation of myeloid cells, myeloid-derived suppressor cells (MDSCs), limit the increase in blood and inflammation in response to three murine models of experimental hypertension [ 25 ]. In a cyclosporine-A model of hypertension, Chiasson et al found that adoptive transfer of MSDCs prevented renal and vascular inflammation and improved vascular relaxation [ 26 ]. More recently, Crowley et al demonstrated that DCs expressing A20, a ubiquitin-editing protein known to preserve immune system hemostasis, abrogates Ang II-induced elevations in blood pressures by preventing renal activated T-cell accumulation [ 20 ], demonstrating a vital role of myeloid cells in the suppression of inflammatory events during hypertensive insults.…”
Section: Novel Immune Cell Subtypes In Hypertensionmentioning
confidence: 99%
“…Treatment of bone marrow-derived macrophages (BMDMs) with tacrolimus significantly inhibited LPS and LPS plus IFN- γ -induced IL-12p40 mRNA and protein expression [ 100 ]. After coculture with increasing concentrations of CsA for 24 h, the number of live splenic MDSCs decreased significantly in a dose-dependent manner by calcineurin inhibition [ 101 ]. In the mouse skin transplant model, a daily dose of 15–30 mg/kg of CsA can promote the accumulation of CD11b + Gr-1 + MDSCs in the graft, draining lymph nodes, spleen, peripheral blood, and bone marrow with the prolonged survival time of grafts [ 102 ].…”
Section: Clinically Used Immunosuppressive Drugs and Their Effectsmentioning
confidence: 99%